Pengembangan Media Buku Huruf untuk Meningkatkan Kemampuan Mengenal Simbol Huruf b dan d pada Anak Usia 4-5 Tahun - Tsani, Hubbi Rossa Nur; Widayati, Sri; Maulidiyah, Eka Cahya; Komalasari, Dewi (UIR PRESS, 2026)
The symbols for the letters b and d in children aged 4-5 years at the RA YKUI Sambogunung institution. Therefore, this research aims to determine the feasibility and effectiveness of letter book media (MEBURU) to improve the ability to recognize letter symbols b and d in children aged 4-5 years. The number of samples used in this research was 21 children. This research uses a type of development research or Research and Development (R&D) to develop products using the ADDIE development model. The results of this research show that the feasibility of the letter book media from media experts gets a percentage value of 96% and material experts get a percentage value of 95%. Meanwhile, the effectiveness of the letter book media (MEBURU) can be seen from the increase in the ability to recognize the letter symbols b and d in children. This assessment can be determined through the Wilcoxon test using IBM SPSS 22 showing that the asymp.sig (2-tailed) value is 0.005 so p < 0.05 or 0.005 < 0.05 then it can be said that Ho is rejected and Ha is accepted which means that there is an average difference between pretest with posttest. So it can be concluded that the use of letter book media (MEBURU) is effective in improving the ability to recognize the letter symbols b and d in children aged 4-5 years. The implication of this research is that children are able to recognize the characteristics of the letters b and d, and children are able to recognize how to write the letters b and d correctly.